Desempenho e características de carcaça de cordeiros de diferentes genótipos, abatidos com três espessuras de gordura subcutânea - Amaral, Rafael Marzall do (2010)
It was evaluated the effects of genotype and fat thickness, determined by ultrasound, on the performance, net income, quantitative and qualitative characteristics of the carcass, physical characteristics of the meat, muscle deposition estimated by the depth of the Longissimus lumborum, and subcutaneous fat deposition of confined lambs. Thirty six lambs were used, 12 of each genotype: Santa Inês (SI), ½ Dorper-Santa Inês (½ D-SI) and ½ White Dorper-Santa Inês (½ WD-SI), slaughtered with three different of subcutaneous fat thickness. The lambs were fed with total ration calculated for daily weight gain of 0.3 kg. Ultrasound evaluations (between the 12th and the 13th ribs) and weightings were carried out each seven days; the slaughter occurred as the lambs reached the predetermined fat thickness: 2.0, 2.5 and 3.0 mm. The daily weight gain was greater for the ½ D-SI (0.311 kg) and ½ WD-SI lambs (0.319 kg). The confinement of the ½ WD-SI (R$ 2,301.60) and ½ D-SI (R$1,911.75) resulted in greater net income than that of SI lambs (R$ 856.60). The lambs slaughtered with 3.0 mm fat thickness had greater body weight, hot and cold carcass weight, index of compactness of the carcass and leg, and lower proportion of second-rank meat, when compared to those slaughtered with 2.0 mm. The indices of compactness of the carcass and leg were better for the crossed lambs, being 14.28 % and 12.24 % higher, respectively. It was verified a greater proportion of first-rank meat for the ½ D-SI and ½ WD-SI lambs. The carcasses of the ½ D-SI and ½ WD-SI lambs did not differ (P>0.05) in any characteristic. To check for differences in the development of the subcutaneous fat (SFT) and Longissimus lumborum muscle depth (LMD), both were evaluated through ultrasound as a function of the confinement period for each genotype. A normal distribution of SFT and LMD was assumed for the Bayesian analysis. The equation obtained for weight gain as a function of the confinement period described a better initial coefficient (b0) for the SI lambs (17.99), followed by ½ D-SI (20.57) and ½ WD-SI (21.65), with higher b1 coefficient for ½ D-SI (0.04) and lower for SI (0.03). The deposition rate (b1) of SFT as a function of the confinement period was higher for ½ D-SI (0.038) and ½ WD-SI (0.039) compared with SI (0.037), indicating an earlier maturity of this characteristic in the crossed lambs. The evaluation of the LMD indicated higher muscle deposition rate (b1) in the SI lambs (0.072) compared to ½ D-SI (0.057) and ½ WD-SI (0.057), which deposited a larger amount of muscle at an earlier phase of life.